Berpikir Positif untuk Menurunkan Stres Psikologis - Enik Nur Kholidah; Asmadi Alsa (Faculty of Psychology, Universitas Gadjah Mada, 2012)
The purpose of this research was to test the effectiveness of training on positive thinking for reducing student’s stress level. The proposed hypothesis was that “Positive thinking training is effective for reducing students’ stress level”. The subjects of the research were 48 students from the Faculty of “P” of “K” University in Yogyakarta. They were divided into two groups, namely experimental group and control group. Each group consisted of 24 students. The experimental design used in the research was the pretest-posttest control group design. Herewith, the experimental group received treatment in the form of training on positive thinking. The students’ stress level scale (SSLS) was used to reveal whether they experienced stress disorder or not. After receiving the positive thinking training, it revealed that the stress level of the experimental group decreased compared with that of the control group (waiting list) that did not receive the training. The T-test done by analyzing the gained score differences between experimental group and control group indicated that the positive thinking training is effective for reducing students’ stress level. It was shown that the result of t count of gained score data (the increasing of positive thinking) amounts 8.232 with p=0.001 and of the reducing of positive thinking amounts -8.148 with p=0.001. Keywords : students’ stress level, positive thinking, positive thinking training.